CTE Workshop Proc. 2022
DOI: 10.55056/cte.124
|View full text |Cite
|
Sign up to set email alerts
|

Immersive learning technology for ensuring quality education: Ukrainian university case

Abstract: The article considers the problem of using immersive learning in the educational and scientific activities of the university. Literature survey revealed that there is a need for an integrated approach for introduction of immersive learning at the university. It involves the creation of a specialized laboratory of virtual and augmented reality with appropriate technical equipment, introduction of immersive learning methodology in university educational programs, development of software and hardware solutions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This article highlights further research by the authors, begun in [222,223,224,225,226,227,228,229,230]. The article "Immersive learning technology for ensuring quality education: Ukrainian university case" [231] by Volodymyr O. Liubchak, Yurii O. Zuban and Artem E. Artyukhov (figure 24) considers the problem of using immersive learning in the educational and scientific activities of the university. Literature survey revealed that there is a need for an integrated approach for introduction of immersive learning at the university.…”
Section: Session 6: Immersive Technology Applications In Educationmentioning
confidence: 98%
“…This article highlights further research by the authors, begun in [222,223,224,225,226,227,228,229,230]. The article "Immersive learning technology for ensuring quality education: Ukrainian university case" [231] by Volodymyr O. Liubchak, Yurii O. Zuban and Artem E. Artyukhov (figure 24) considers the problem of using immersive learning in the educational and scientific activities of the university. Literature survey revealed that there is a need for an integrated approach for introduction of immersive learning at the university.…”
Section: Session 6: Immersive Technology Applications In Educationmentioning
confidence: 98%
“…By effectively utilising these technologies, universities may give students a more immersive and engaging learning environment that mimics a traditional laboratory setting (Liubchak, Zuban & Artyukhov 2022). Furthermore, faculty, staff and students must take personal responsibility for training themselves in using technology and consistently upgrading their skills and knowledge.…”
Section: Investing In Technologymentioning
confidence: 99%
“…The authors' related works are referenced as [13,81,131]. The paper "Evaluation of the system "quality of education" and its socio-economic impact: analogies with software testing" [10] by Artem Artyukhov (figure 6), Iurii Volk, Nadiia Artyukhova, Roman Halenin and Liudmyla Batsenko presents a reliable algorithm for testing the quality of education systems and its relationship with sustainable development goals.…”
Section: Articles Overview 21 Digital Transformation Of Educationmentioning
confidence: 99%